High cycle torsional fatigue properties of 17-4PH stainless steel - K. Yanase; B.M. Shönbauer; M. Endo (Fracture and Structural Integrity)
Sensitivity to small defects under torsional fatigue loading condition is examined in the high cycle fatigue regime. Fatigue crack initiation and small crack growth behaviors were observed during fatigue testing and fractographic investigations were performed. The results are compared to the data obtained in the uniaxial fatigue tests, which allows the effect of biaxial stresses on the surface of material to be discussed. Finally, an approach for predicting the fatigue limit of 17-4PH stainless steel under torsional and tension-compression fatigue loadings is presented.